Location Tracking, Messaging, and Monitoring System for Lightweight Boats Using LoRa Technology ‘Safe Ride’ - Alweera A.M.H.M; Wijesinghe H.W.M.V.A; Chandrasiri R.M.S; De Silva W.A.D.S; Ishara Gamage; Thusithanjana Thilakarathna (International Journal of Engineering and Management Research, 2022)
The facilitation of maritime communications has been a challenging endeavor from the beginning of history. Coverage for maritime communications is limited due to the limited availability of various communication solutions. They rely on intercontinental telecommunications satellites. Typically, ships have reliable communication options because of satellite technology. Since these systems are both costly and drain substantial amounts of power from the terminals, only lightweight boats do not utilize them. Lightweight boat sailors typically encounter numerous challenges due to a failure to effectively communicate. Therefore, individuals face numerous risks in unexpected situations. Although radio transmission technologies such as Wi-Fi, 4G, WiMAX, etc. have advanced rapidly in recent times, seaside communications remain challenging due to poor transmission conditions, coastal interference, and a lack of pre-installed machinery to facilitate long-range interconnection with the land. Fortunately, this problem has a highly efficient answer: the Low Power—Wide Area Network (LP-WAN). This approach is well-liked for Internet of Things (IoT) uses since it allows for extended transmissions of more than 15 km (10 miles) in empty space while only requiring a small amount of power. LoRa (Long Range) is a popular example of a low-power wide-area network. This study's ultimate goal is to use LoRa mesh networking technology for the development of a network in a coastal environment. So, we might be able to keep good connections to land while reducing the number of accidents involving light boats.